A Novel Mutation in STXBP1 Gene in a Child With Epileptic Encephalopathy and an Atypical Electroclinical Pattern. (February 2014) - Romaniello, Romina; Zucca, Claudio; Tenderini, Erika; Arrigoni, Filippo; Ragona, Francesca; Zorzi, Giovanna; Bassi, Maria Teresa; Borgatti, Renato
Mutations in STXBP1 gene, encoding the syntaxin binding protein 1, have been recently described in Ohtahara syndrome, or early infantile epileptic encephalopathy with suppression-burst pattern, and in other early-onset epileptic encephalopathies. A 3-year-old boy affected by epileptic encephalopathy started at 8 months of age is described. Focal epilepsy was characterized by drug resistance seizures with multifocal interictal and ictal electroencephalographic (EEG) features and variable EEG focus. Direct sequencing of the STXBP1 gene showed a novel de novo mutation (c.751G>A), leading to a p.Ala251Thr substitution. Based on reported data, treatment with vigabatrin was attempted and patient became immediately seizure free for 4 months. The present case further expands the clinical spectrum of " STXBP1 -related encephalopathy" suggesting molecular analysis of STXBP1 in early onset epileptic encephalopathies of unknown etiology (with onset within the first year of life). In addition, the case provides valuable suggestions on seizures treatment in STXBP1 mutated subjects.